A flexible e-voting scheme for debate tools. Issue 56 (February 2016) - López García, D.A.
Abstract: In order to protect votes, e-voting schemes provide privacy, verifiability and eligibility among other features. Most e-voting systems focus on the vote itself, considering it a fixed and limited piece of data (e.g. choosing from a list of candidates) which has to be encrypted and repeatedly permuted. In recent years, collective decision systems have been developed in which participants can submit proposals, argue and vote. In these systems the information to be protected is variable and plentiful, inaccessible to classic methods. The scheme proposed in this paper has been designed to cover these needs. Using the technique of blind signature, an alias is granted to the user that guarantees privacy. The novelty is that this alias consists of a public key that gives users the ability to encrypt and sign. From this alias users can access to the system and operate as if no privacy were needed, which greatly simplifies the process of voting, validation and counting. In addition, this article details one improvement that makes the scheme resistant to coercion.